The Responsibility of Local Governments in Protecting Water Resources - Youssef Abdullah, Researcher. Hassan; Soha Zaki Nouri, Assist .Prof. (Basra studies journal, 2025)
Water resources form a fundamental basis for industrial, social, and economic development. These resources are diverse and include rainfall, rivers, lakes, seas, and especially international rivers. The issue of water resources is a major point of focus in international relations, particularly because many watercourses are shared by more than one country. Some countries have built dams that affect the water inflows of other nations sharing the same river systems. Iraq is among the countries most affected by this issue. Given Iraq’s significant dependence on shared water resources most notably the Tigris and Euphrates rivers and the increasing water scarcity it faces, it has become imperative to regulate the use of water and prevent potential conflicts through international agreements. The responsibility for addressing these challenges lies with the Iraqi federal government, particularly the executive and legislative branches, which must develop appropriate policies and solutions to manage and protect the country’s water resources effectively.